TheSimulation of Numerical Method of Finite Difference for Predicting the Distribution of Volumetric Water and Water Potential - Tamrin Latief; . Hermantoro; Budi Indra Setiawan (PERTETA, 2000)
This paper describes an application of n rmerical method of finilsdzflerence for predicting the distribution of volumetric water (8) and water potential (v by using diffusity and conductivity approach. The result of current study showed that the parameters, volumetric water and water potential, correlated reversely. The trend of application of numerical method was similar to that of exact method. The simulation of parameters was not signiJcant. The reliability of models is still needed to test emperically.